Heterosis and combining ability for yield traits and its relationship with gene action in muskmelon (Cucumis melo) - SAHA, KOUSHIK; CHOUDHARY, HARSHAWARDHAN; MUNSHI, A D; SINGH, A K (The Indian Journal of Agricultural Sciences, 2022)
Twenty-one F1 hybrids were developed from seven diverse parental lines of muskmelon (Cucumis melo L.) from two horticultural groups, viz. inodorous and cantalupensis through half-diallel mating system and evaluated at ICARIndian Agricultural Research Institute, New Delhi, during 2017 and 2018. The component of variance for sca (σ2s) was higher than gca component of variance (σ2g) for all the characters, except average fruit weight, which indicated the importance of non-additive gene action for improvement of many traits. The predictability ratio and average degree of dominance was less than 0.5 and more than 1 for all the yield related traits, except average fruit weight, which further confirmed the predominant role of non-additive component of variance. The parent DHM-163 (P1) was identified as good general combiner for earliness, whereas parent DCM-31 (P4) for fruit length, average fruit weight and yield per plant. The parent Pusa Madhuras (P5) also exhibited highest gca effects for number of fruits per plant, number of primary branches per plant, fruit diameter and negative gca effects for days to first fruit harvest. The hybrid DCM-31 × Kashi Madhu (P4 × P6) exhibited highest heterotic value for days to first male flower anthesis, days to first female flower anthesis and days to first fruit harvest. Three crosses, DMM-159 × Pusa Madhuras (P3 × P5), DHM-163 × Kashi Madhu (P1 × P6) and DMM-159 × DCM-31 (P3 × P4) were found to be best heterotic combinations for yield related traits. These promising heterotic hybrid combinations may be tested under multi-location trials to assess their potential as commercial hybrids.